1960
DOI: 10.1172/jci104046
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Endotoxin by a Humoral Component. Vi. Two Separate Systems Required for Viable and Killed Salmonella Typhosa

Abstract: The blood of mammalian species contains a component which inactivates endotoxins in vitro (1). This endotoxin-detoxifying component (EDC) is identified by attributes which distinguish it from other substances in blood of known biologic activity (2, 3). Following appropriate interaction in vitro with this component, endotoxins from gram-negative bacteria are so altered that they no longer elicit such characteristic host reactions as the production of antibody (4), tumor damage, local skin reactivity and fatal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1960
1960
1986
1986

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The bactericidal action of fresh normal serum on gram-negative bacteria is attributable to a system comprised of specific antibody, the recognized components of complement, and divalent cation. The essential findings of a previous studv (Landy, Trapani, and Rosen, 1960), which detailed these requirements for S. t!lphosa 0901, are summarized in removal, inactivation, or complexing of any of the components of this system results in loss of bactericidal activity. When all other components were present in excess, as little as 0.002 iAg of antibody N was sufficient to fully restore bactericidal activity to the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bactericidal action of fresh normal serum on gram-negative bacteria is attributable to a system comprised of specific antibody, the recognized components of complement, and divalent cation. The essential findings of a previous studv (Landy, Trapani, and Rosen, 1960), which detailed these requirements for S. t!lphosa 0901, are summarized in removal, inactivation, or complexing of any of the components of this system results in loss of bactericidal activity. When all other components were present in excess, as little as 0.002 iAg of antibody N was sufficient to fully restore bactericidal activity to the system.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations which reaffirmed the specificity of the antibody requirement have, in addition, shown that the quantity of this component which suffices to restore bactericidal activity to absorbed serum is exceedingly small (Muschel and Treffers, 1956;Landy, Trapani, and Rosen, 1960). It was this minimal antibody requirement which suggested to us that the bactericidal system could be utilized for the detection and measurement of the small amounts of antibody present in normal serum.…”
mentioning
confidence: 94%